HSF1 is essential for the resistance of zebrafish eye and brain tissues to hypoxia/reperfusion injury. - Nathan R Tucker; Ryan C Middleton; Quynh P Le; Eric A Shelden (PLoS ONE)
Ischemia and subsequent reperfusion (IR) produces injury to brain, eye and other tissues, contributing to the progression of important clinical pathologies. The response of cells to IR involves activation of several signaling pathways including those activating hypoxia and heat shock responsive transcription factors. However, specific roles of these responses in limiting cell damage and preventing cell death after IR have not been fully elucidated. Here, we have examined the role of heat shock factor 1 (HSF1) in the response of zebrafish embryos to hypoxia and subsequent return to normoxic conditions (HR) as a model for IR. Heat shock preconditioning elevated heat shock protein expression and protected zebrafish embryo eye and brain tissues against HR-induced apoptosis. These effects were inhibited by translational suppression of HSF1 expression. Reduced expression of HSF1 also increased cell death in brain and eye tissues of embryos subjected to hypoxia and reperfusion without prior heat shock. Surprisingly, reduced expression of HSF1 had only a modest effect on hypoxia-induced expression of Hsp70 and no effect on hypoxia-induced expression of Hsp27. These results establish the zebrafish embryo as a model for the study of ischemic injury in the brain and eye and reveal a critical role for HSF1 in the response of these tissues to HR. Our results also uncouple the role of HSF1 expression from that of Hsp27, a well characterized heat shock protein considered essential for cell survival after hypoxia. Alternative roles for HSF1 are considered.